Studium reakce 8-aminochinaldinu s tetrahalogenovanými ftalanhydridy - Horáčková, Pavlína (Univerzita Pardubice, 2007)
Studium reakce 8-aminochinaldinu s tetrahalogenovanými ftalanhydridy.
Research of Reaction of 8-Aminoquinaldine with Tetrahalogenated Phtalanhydrides